Collaborative Design as a Context for Teacher and Researcher Learning: Introduction to the Special Issue - Goldman, Susan R.; Hmelo-Silver, Cindy E.; Kyza, Eleni A. (My University, 2022)
This special issue joins the recent but growing effort to expand knowledge in the learning sciences, by examining the notion of participation in teacher-researcher collaborative design (co-design). Co-design is not just a means to an end; it is a context where professional learning happens. Each of the seven papers describes teacher-researcher collaborations focusing on the professional learning of both teachers and researchers engaged in jointly designing learning environments. Central questions of interest are: What do teachers and researchers learn from each other, how, and why? What kinds of activities and opportunities support what kinds of learning and for whom? What can we learn from these collaborations about how to support these partnerships? The commentary addresses the importance of both multiple perspectives (alterity, meaning that the researcher and teacher perspectives are distinct), their affinity (common purpose), and the mutuality that these entail.
Keywords: Teacher; Researcher Learning; Collaborative Design